Recent Advances in Chitosan and its Derivatives in Cancer Treatment - Ding, Jingxian; Guo, Yonghong (Frontiers in Pharmacology, 2022)
Cancer is a major public health problem worldwide. The conventional treatment measures for cancer include surgery, radiotherapy and chemotherapy. Among the various available treatment strategies, chemotherapy remains one of the most important treatment approaches for most of cancer patients. However, chemotherapy for most cancers still faces many problems associated with reversible and irreversible adverse effects, which limit its therapeutic efficacy, low survival quality and discount cancer prognosis. To minimize these side effects and improve therapeutic potency and patient compliance, more targeted therapies are highly desirable. Sustainable and controlled deliveries of drugs with controllable toxicities are expected to address these hurdles. Chitosan is the second most abundant natural polysaccharide, which has excellent biocompatibility and notable antitumor activity. Its biodegradability, biocompatibility, biodistribution, nontoxicity and immunogenicity free have made chitosan an appreciated polymer with numerous applications in the pharmacology, especially in oncotherapy. In the present review, we provide an overview of the main advances in chitosan and its derivatives in pharmacology with a special focus on their agents delivery applications, immunomodulation, signal pathway modulation and antitumor activity to highlight their role in cancer treatment. Despite a great number of successful investigations, commercialization of chitosan copolymers still remains a challenge. Further advancements in polymerization techniques may address the unmet needs of the healthcare industry.